Metasurface-enhanced optical lever sensitivity for atomic force microscopy. (17th June 2019) - Yao, Zan; Xia, Xicheng; Hou, Yaoping; Zhang, Peng; Zhai, Xiaomin; Chen, Yuhang
Abstract: We proposed the integration of metasurfaces on atomic force microscopy (AFM) cantilevers to improve the optical lever sensitivity. The metasurface positioned at the back of an AFM cantilever enables anomalous reflection of the laser beam and provides a nonlinear relationship between the incidence and reflection angles following the generalized Snell's law. Therefore, the displacement of the reflected laser spot at the photodetector can be amplified. The metasurface was composed of 30 nm thick Au nano-discs with different diameters in an array of 1500 nm × 300 nm super cells. Using the fabricated metasurface mounted on a precise angle dial and a macroscale cantilever as prototypes, the concept of a metasurface-enhanced cantilever was experimentally ascertained. Results proved that the optical lever sensitivity can be easily increased. Finite element analysis showed that integration of the thin metasurface does not have a significant impact on the cantilever's mechanical properties including stiffness and eigenfrequencies. The proposed metasurface-enhanced optical lever sensitivity may have potential applications in improving functional performances of AFM instruments and cantilever-based sensors, such as allowing much smaller imaging forces and boosting the signal-to-noise ratio.